A Love-Based Curriculum is Used at MI Nurul Mun’im to Improve Students’ Empathy - Zaenol Fajri; Nurul Ikhsan (Journal of Basic Education Research, 2026)
Purpose of the study: This study addresses the decline in students’ empathy, marked by increasing individualism and low social awareness. It highlights the need for a love-based curriculum that emphasizes compassion beyond cognitive learning. The study aims to describe the improvement of empathy among fifth-grade students at MI Nurul Mun’im through this approach.. Methodology: . A descriptive qualitative methodology was employed, and data were gathered via observation, interviews, and recording with 34 students, Islamic Religious Education teachers, and the Deputy Curriculum. Data reduction, presentation, and triangulation validity testing were used to analyze the data and derive findings. Main Findings: The findings show that a love-based curriculum can foster humanistic, interactive, and meaningful learning, as well as raise students’ empathy, including cooperation, compassion, and respect for one another. Teacher readiness, madrasah support, and a variety of teaching strategies contributed to this accomplishment, but challenges, including variations in student character, time constraints, and environmental factors, persisted. In conclusion, through a steady process of habituation, the love-based curriculum effectively increases students’ empathy. In the context of Islamic education in particular, this research advances the development of humanitarian-based character education Novelty/Originality of this study: Madrasahs are advised to expand teacher preparation, increase implementation consistency, and carry out additional research to evaluate this strategy’s long-term efficacy.